2016
DOI: 10.1002/anie.201605757
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Supramolecular Receptor for the Hydrosulfide Anion

Abstract: Hydrogen sulfide (H2S) has emerged as a crucial biomolecule in physiology and cellular signaling. Key challenges associated with developing new chemical tools for understanding the biological roles of H2S include developing platforms that enable reversible binding of this important biomolecule. Here we report the first synthetic small molecule receptor for hydrosulfide anion, HS−, solely utilizing reversible, hydrogen-bonding interactions in a series of bis(ethynylaniline) derivatives. Binding constants up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 38 publications
4
36
0
Order By: Relevance
“…12c could bind the highly nucleophilic hydrosulfide anion (HS − , conjugate base of hydrogen sulfide, H 2 S). 56 These studies revealed that a short CH•••S contact contributed to the strong association of hydrosulfide in these complexes, and solution phase measurements supported the existence of this HB as well. In a continued attempt to determine the contribution of aryl CH hydrogen bonds in anion binding, the Pluth group published a series of tribenzamide TREN-based receptors (Fig.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…12c could bind the highly nucleophilic hydrosulfide anion (HS − , conjugate base of hydrogen sulfide, H 2 S). 56 These studies revealed that a short CH•••S contact contributed to the strong association of hydrosulfide in these complexes, and solution phase measurements supported the existence of this HB as well. In a continued attempt to determine the contribution of aryl CH hydrogen bonds in anion binding, the Pluth group published a series of tribenzamide TREN-based receptors (Fig.…”
mentioning
confidence: 76%
“…In one case, these pursuits led us to report the first examples of supramolecular receptors for the reversible binding of biologically-critical yet highlyreactive hydrosulfide (HS − ) anion. 56 Subsequent to these studies, new receptors targeting these types of biologically relevant anions through the use of aryl CH HBs have appeared. 49,57 We are now further exploring the use of aryl CH hydrogen bonds to bind other reactive, yet biologically-relevant (hydro)chalcogenide anions, including hydroselenide and hydrogen sulfate.…”
Section: Our Future In the Field Of Aryl Ch•••anion Hydrogen Bondingmentioning
confidence: 99%
“…Additional stabilizing forces in the lattice include C-H hydrogen bonds from the methyl (3.7 Å) and meta aryl (3.9 Å) hydrogens, consistent with recent work demonstrating that sulfur is a C-H hydrogen bond acceptor. 27 …”
mentioning
confidence: 99%
“…Towards this aim, our lab has developed several arylethynyl frameworks (Figure 1) capable of binding a variety of anionic guest molecules, including halides, [14][15][16][17][18] oxoanions, [19][20][21] and hydrochalcogenides. [22][23][24] These hosts take advantage of both their multidentate binding pockets formed from the meta-substitution of the phenyl or pyridyl cores with two arylethynyl arms as well as the fluorescent nature of the -conjugated backbone.…”
Section: Introductionmentioning
confidence: 99%
“…14 This opened a floodgate of 13 eventual co-advised students and postdocs over the next 14 years who explored anion--interactions, the effect of increasing or reducing the number of urea binding units, the effects of different heterocyclic cores, and the physical organic chemistry of these receptors and their guests. 16,[19][20][21][22][23][24] Along the way, graduate student Blake Tresca further improved upon the early designs by replacing the pH-sensitive pyridine core with a benzene as in 2 and showed that the C-H•••anion interaction could be tuned by installing electron-donating/electron-withdrawing groups para to the CH unit. 26 the National Academy of Inventors.…”
Section: Introductionmentioning
confidence: 99%